2015
DOI: 10.1371/journal.pone.0136962
|View full text |Cite
|
Sign up to set email alerts
|

The Perfect Burrow, but for What? Identifying Local Habitat Conditions Promoting the Presence of the Host and Vector Species in the Kazakh Plague System

Abstract: IntroductionThe wildlife plague system in the Pre-Balkhash desert of Kazakhstan has been a subject of study for many years. Much progress has been made in generating a method of predicting outbreaks of the disease (infection by the gram negative bacterium Yersinia pestis) but existing methods are not yet accurate enough to inform public health planning. The present study aimed to identify characteristics of individual mammalian host (Rhombomys opimus) burrows related to and potentially predictive of the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Clay loam soils have almost equal parts of sand and silt, with a slightly higher percentage of clay. The higher percentage of clay in the soil may confer the advantage of a more stable and long-term burrow, while the equal percentages of sand and silt may make the initial excavating of the burrow easier and more energy efficient (Levick et al 2015). This corresponds well to the findings of Proulx et al ( 2012), who showed that ground squirrels were mostly limited to the Brown soil zone which is typically composed of loam or coarser texture soils.…”
Section: Discussionsupporting
confidence: 85%
“…Clay loam soils have almost equal parts of sand and silt, with a slightly higher percentage of clay. The higher percentage of clay in the soil may confer the advantage of a more stable and long-term burrow, while the equal percentages of sand and silt may make the initial excavating of the burrow easier and more energy efficient (Levick et al 2015). This corresponds well to the findings of Proulx et al ( 2012), who showed that ground squirrels were mostly limited to the Brown soil zone which is typically composed of loam or coarser texture soils.…”
Section: Discussionsupporting
confidence: 85%
“…Great gerbil burrows vary in depth up to 3 m, and the depth is critical to flea survival, with shallow burrows less favorable for fleas (96, 97). Burrows in sandy soil and those surrounded by vegetation may be more likely to contain plague-bearing fleas (9). Using PCR assays (98), Y. pestis can be more sensitively detected in burrow-collected fleas, and flea species more likely to contribute to plague persistence locally can be identified.…”
Section: Accepting Plague Persistencementioning
confidence: 99%
“…Y. pestis has been detected in over 280 species and subspecies of fleas associated with rodent colonies in these areas (8). While the factors constraining where plague reservoirs may exist are not fully known (9), certain rodent species appear to be cornerstone hosts for the disease (10). In our current understanding, plague persists within these ecosystems in a continuous exchange of Y. pestis between rodent individuals, with fleas as the main vector (11).…”
mentioning
confidence: 99%
“…The study sites concerned randomly chosen 500 m × 500 m (25 ha) squares spread over 6 sectors (see Fig. 4.2) (Levick et al 2015).…”
Section: Methodsmentioning
confidence: 99%